Construction of a high-resolution genetic map and identification of single nucleotide polymorphism markers relevant to flower stalk height in onion - Li, Yanwei; Huo, Yumeng; Yang, Yanyan; Wang, Zhenbao; Sun, Yaling; Liu, Bingjiang; Wu, Xiong (Frontiers in Plant Science, 2023)
Onion (Allium cepa L., 2n=16) is an economically and nutritionally important vegetable crop worldwide. Construction of a high-resolution genetic map and map-based gene mining in onion have lagged behind other vegetable crops such as tomato and pepper. In this study, we constructed a high-resolution genetic map of onion using 321 F2 individuals from a cross between two double haploid lines DH-1×DH-17 and employing specific length amplified fragment (SLAF)-seq technology. The genetic map containing 10,584 polymorphic SLAFs with 21,250 single nucleotide polymorphism (SNP) markers and 8 linkage groups was developed for onion, which spanned 928.32 cM, with an average distance of 0.09 cM between adjacent markers. Using this map, we carried out Ms QTL locus related to the male-sterile trait and reproduced previous mapping results, which proved that this map was of good quality. Then, four QTLs (located on LG2, LG5, and LG8) were detected for flower stalk height, explaining 26.60% of the phenotypic variance. Among them, we proposed that 20 SLAF markers (in three QTLs) of flower stalk height trait were effective favorable allelic variants associated with heterosis. Overall, the genetic map was structured using SLAF-seq based on DH lines, and it is the highest-quality and highest-resolution linkage map of onion to date. It lays a foundation for the fine mapping and candidate gene identification of flowering stalk height, and provides new insights into the developmental genetic mechanisms in onion breeding.